Erythrocyte membrane biomimetic EGCG nanoparticles attenuate renal injury induced by diquat through the NF-κB/NLRP3 inflammasome pathway - Qu, Jie; Pei, Hui; Li, Xin-Ze; Li, Yan; Chen, Jian-Ming; Zhang, Min; Lu, Zhong-Qiu (Frontiers in Pharmacology, 2024)
This study sought to investigate the therapeutic effect and mechanism of red blood cell membrane (RBCm) biomimetic epigallocatechin gallate (EGCG) nanoparticles (NPs) (EGCG-RBCm/NPs) on renal injury induced by diquat (DQ). Human renal tubular epithelial cells (HK-2 cells) were stimulated with 600 μM DQ for 12 hours and mice were intraperitoneally injected with 50 mg/kg b.w. DQ, followed by 20 mg/kg b.w./day EGCG or EGCG-RBCM /NPs for 3 days. The assessment of cellular vitality was carried out using the CCK-8 assay, while the quantification of reactive oxygen species (ROS) was performed through ROS-specific probes. Apoptosis analysis was conducted by both flow cytometry and TUNEL staining methods. Pathological changes in renal tissue were observed. The expressions of NLRP3, IL-1β, IL-18, NFκB and Caspase1 were detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR), immunohistochemistry, immunofluorescence, and western blot. The results showed that the DQ group had increased ROS expression, significantly increased malondialdehyde (MDA) levels, decreased superoxide dismutase (SOD) activity, and increased apoptosis rate compared with the control group. Histopathological analysis of mice in the DQ group showed renal tubular injury and elevated levels of blood urea nitrogen (BUN), serum creatinine (SCr), kidney injury molecule-1 (KIM-1), and cystatin C (Cys C). Furthermore, the DQ group exhibited heightened expression of NLRP3, p-NFκB p65, Caspase1 p20, IL-1β, and IL-18. However, EGCG-RBCm/NPs treatment mitigated DQ-induced increases in ROS, apoptosis, and oxidative stress, as well as renal toxicity and decreases in renal biomarker levels. Meanwhile, the expression levels of NLRP3, p-NFκB p65, Caspase1 p20, IL-1β, and IL-18 were significantly decreased, and the survival rate of mice was ultimately improved, with an effect better than that of the EGCG treatment group. In conclusion, EGCG-RBCm/NPs can improve oxidative stress, inflammation, and apoptosis induced by DQ. This effect is related to the NF-κB/NLRP3 inflammasome pathway. Overall, this study provides a new approach for treating renal injury induced by DQ.